Rubber tree (Heyea spp.) mini-grafting. II. Problems and technical advances - Lemos Filho, José Pires de; Pereira, Jomar da Paes; Medrado, Moacir Sales; Costa, José Dias; Pinto, Hilton silveira (Pesquisa Agropecuaria Brasileira, 1994)
With the aim of contributing to the technical viability of rubber tree mini-grafting, standard techniques were altered, including modifications on the graft fixation system, irrigation scheme and development of sprout disinfection. These alterations resulted in reduction of time of grafting, maintenance space of grafted plants, and reduction in mortality caused by fungi.